Ventricular Tachycardia due to an Overdose of Tibetan Drugs: A Case Report of Aconitine Poisoning - Panjing Liu; Mingyuan Niu; Xiaobin Zhang; Hui Han (Clinical Case Reports)
ABSTRACT Tibetan medicine enjoys a high recognition among Tibetans. Many Tibetan hospitals and medicine shops are dedicated to related research and prescribe Tibetan drugs to patients. Overdose intake of aconite‐containing Tibetan drugs might cause severe poisoning manifesting malignant ventricular arrhythmias. Supportive measurements, including external chest compression, electric cardioversion, fluid resuscitation, and intravenous administration of amiodarone/lidocaine, aim at restoring sinus rhythm, serving as “time‐buying” mechanisms to allow the body to naturally excrete the toxic alkaloids.